INTERNATIONAL LAW AND THE ROLE OF THE STATE OF INDONESIA IN ASEAN AS A CONFLICT MEDIUM ON SOUTH CHINA SEA ISSUES - Dewa Gede Sudika Mangku; Muhammad Adam Firdaus; Ni Luh Wayan Yasmiati (Jurnal Komunikasi Hukum, 2022)
This study discusses the role of Indonesia as a conflict mediator on the issue of the development of problems related to the sovereignty conflict of China which claims most of the South China Sea zone. This problem received intervention from a third country, one of which was the United States. Indonesia and other ASEAN member countries that claim parts of the South China Sea against China's policies are still in the discussion process and in the process of signing the draft SCS Code of Conduct with China.